Biomarkers of endothelial activation and dysfunction in cardiovascular diseases - Zhang, Jun (Reviews in cardiovascular medicine, 2022)
Endothelial activation and dysfunction is an important contributor to atherosclerosis, cardiovascular diseases and cardiorenal syndrome. Endothelial dysfunction is also linked with metabolic syndrome and type II diabetes. The search for specific and sensitive biomarkers of endothelial activation and dysfunction may have important clinical implications. This review pinpoints the differences in biomarkers between endothelial activation and endothelial dysfunction in cardiovascular diseases, and then briefly describes the most relevant biomarkers of endothelial activation. Biomarkers of endothelial activation include endothelial adhesion molecules, cytokines, C-reactive protein, CD62E+/E-selectin activated endothelial microparticles, oxidation of low density lipoproteins, asymmetric dimethylarginine and endocan. This review also presents an update on the novel biomarkers of endothelial dysfunction, such as matrix metalloproteinases (e.g., MMP-7, MMP-9), ANGPTL2, endogdlin, annexin V+ endothelial apoptotic microparticles, and serum homocysteine. Finally, this review emphasizes the limitations of biomarkers of endothelial activation and dysfunction in clinical setting.